Influence of electrostatic interactions on the release of charged molecules from lipid cubic phases - Negrini, Renata (Langmuir : the ACS journal of surfaces and colloids, 2014)
The release of positive, negative, and neutral hydrophilic drugs from pH responsive bicontinuous cubic phases was investigated under varying conditions of electrostatic interactions. A weak acid, linoleic acid (LA), or a weak base, pyridinylmethyl linoleate (PML), were added to the neutral monolinolein (ML) in order to form lyotropic liquid-crystalline (LLC) phases, which are negatively charged at neutral pH and positively charged at acidic pH. Release studies at low ionic strength (I = 20 mM) and at different pH values (3 and 7) revealed that electrostatic attraction between a positive drug, proflavine (PF), and the negatively charged LLC at pH = 7 or between a negative drug, antraquinone 2-sulfonic acid sodium salt (AQ2S), and the positively charged LLC at pH = 3 did delay the release behavior, while electrostatic repulsion affects the transport properties only to some extent. Release profiles of a neutral drug, caffeine, were not affected by the surface charge type and density in the cubic LLCs. Moreover, the influence of ionic strength was also considered up to 150 mM, corresponding to a Debye length smaller than the LLC water channels radius, which showed that efficient screening of electrostatic attractions occurring within the LLC water domains results in an increased release rate. Four transport models were applied to fit the release data, providing an exhaustive, quantitative insight on the role of electrostatic interactions in transport properties from pH responsive bicontinuous cubic phases